Dialog Insekuritas Pangan Berdasarkan Kajian Keamanan Internasional: Gugatan Pendekatan Kritis Terhadap Pendekatan Arus-Utama - Aspin Nur Arifin Rivai (UIN ALAUDDIN MAKASSAR, 2020)
This article is a theoretical review based on idea comparisons in exploring various perspectives on food insecurity. Overall, the authors focus on the discussion of food insecurity, in the form of hunger which is considered to have several limitations. The narrative or discursive of food security and food sovereignty contradicts one another. Even so, the two are not as oppositional concepts, but as interrelated concepts, especially covering efforts to overcome hunger which includes access, distribution, security and equality. Meanwhile, the approach to national security based on realism and human security based on the Copenhagen School has significant differences. However, both have problems in positioning hunger as a security issue. Realism that relies on the state-centric places dealing with hunger is the concentration of government activities in ensuring national interests, so that the existing policies are on how the food availability can be fulfilled or surplus. Subsequently, the human security perspective looks at the hunger issue faced by humans so that a securitization process is needed that is carried out by securitization agency. It can be seen here that actions to overcome fundamental problems are only the responsibility of the elite governments, while the voices of the interests of individuals experiencing hunger are neglected. Thus, a critical security approach appears to mediate the above limitations. This perspective offers that the issue of hunger should be reframed as this security problem is a structural problem. Furthermore, this approach proposes the definition of food security in vulnerable populations from the structural violence of hunger.